Stagnation point flow and heat transfer over a stretching or shrinking sheet in a porous medium - Japili, Nirwana (2021)
The steady stagnation point flow towards a stretching/shrinking sheet in a porous medium is investigated. Mathematical models are derived for stagnation point flow and heat transfer problems towards a linearly and exponentially stretching or shrinking sheet in a porous medium in the presence of magnetohydrodynamics, suction and slip effect at the surface. Similarity transformations are used to transform the partial differential equations into a nonlinear ordinary differential equation. These equations are numerically solved by using a shooting method in Maple software. Results for the skin friction coefficients, local Nusselt number, velocities and temperature profiles are presented using graphs with respect to the involved parameters of interest, including stretching or shrinking parameter c, suction parameter s, magnetic parameter M, permeability parameter K, velocity slip parameter A and thermal slip parameter B. The findings of the present work reveal that the magnitude of the skin friction coefficients and the local Nusselt number which reflects the rate of heat transfer at the surface are strongly dependent on these parameters. Besides, for a certain range of the shrinking parameter, dual solutions exist. It is also observed that in the exponentially shrinking sheet case, the solutions’ domain is greater than in the linear case.